ANALISA KROM TOTAL DI DAERAH INDUSTRI TENUN SONGKET SUNGAI MUSI KOTA PALEMBANG (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2016)
Research on Chromium Analysis Total Regional Industrial Weaving Songket Palembang Musi River has been carried out in July and August 2013. This study aims to determine the concentration of total chromium (Cr-T) in the three sampling sites were in the vicinity of the domestic weaving industry songket Palembang Musi River. the results obtained by the average concentration of total chromium (Cr-T) at three sampling locations at 0.8094 mg / L and an average pH of the third water sampling locations ranging from 6.8. Based on South Sumatra Governor Regulation No. 18 In 2012, the average concentration of total chromium at three sampling locations are around the area songket Palembang Musi River is still below the standard that is below 1 mg / L.Â Keywords: chrome total, songket weaving industry, The Musi River